A Study on The Combination of Yoga Practices and Varma Therapy for Controlling Depression and Improving Self Confidence Among Insomnia Patients - Selvam, A.S.; Yoganandhan, V. (Journal of Neonatal Surgery, 2025)
This study aimed to evaluate the use of Yoga Practices and Varma Therapy combination on Depression and Self-confidence among insomnia patients of middle-age. For this study, thirty insomnia patients aged between 40 and 50 years with their residence in Chennai, were found and grouped in two categories namely, the experimental and control groups of fifteen (15) numbers with a training session of 12 weeks. Depression and Self-confidence were assessed using the Psychological Questioners developed by Beck and Rekha Agnihotri. The experimental group is subjected to yoga practice with Varma therapy for 12 weeks. In that, a maximum of one hour 30 minutes in the morning for six days a week is essential for the control group, such that it is kept in an active rest state. Both the groups are subjected to the pre-test and post-test, which means before and after training of yoga practices with Varma therapy respectively. ANCOVA was used to analyse the data, such that a confidence level of 0.05 is kept for the level of significance. It was concluded that there was a significantly reduced level of Depression and Self-confidence (improved) among middle-aged insomnia patients due to the use of Yoga Practices with Varma Therapy compared to the control group.